Mistakes and quasi mistakes in applying the criminal law: causes and consequences - V. V. Sverchkov (Russian Journal of Economics and Law, 2019)
Objective: to identify the causes of mistakes and quasi-mistakes in applying criminal law; to establish consequences of un- substantiated illegal law-enforcement decisions made by interrogators, investigators, prosecutors, and judges due to mistakes and quasi-mistakes; to elaborate proposals aimed at preventing these mistakes and quasi-mistakes.Methods: analytical, dialectical, dogmatic, documentary, logical, practical, and systematic.Results: the concepts of “mistake in applying criminal law” and “quasi-mistake in applying criminal law” are defined; the causes of the mentioned mistakes and quasi-mistakes are identified; the most harmful consequences are identified, which are related to unsubstantiated illegal law-enforcement decisions made by interrogators, investigators, prosecutors, and judges due to mistakes and quasi-mistakes at law-enforcement and managerial levels of implementing the criminal legal policy of the state; the proposals are formulated to enshrine in the legislation the duty of the law enforcement officer to be responsible for a mistake or quasi-mistake in decision-making and for the negative consequences that have arisen, as well as the proposal to exclude such a duty due to objective circumstances.Scientific novelty: the article for the first time a) defines the concept of “a mistake in applying criminal law” as a neglect in the investigative and judicial practice, inaccuracy, distortion, flaw when classifying a deed under the criminal law, as well as when using the criminal legal measures. Also, b) the author gives the definition of “a quasi-mistake in applying criminal law” as a deliberate making of an illegal, unsubstantiated decision. The reasons of the mentioned mistakes or quasi-mistakes are identified: a) complexity of the specific situations that must be overcome by applying the criminal law; b) low professional level of law enforcers; c) negligence in carrying out the investigation/judicial proceedings due to personal qualities, disruption of work, excessive workload; d) impact on decision making of conjuncture circumstances, opinions/orders of the law-enforcement body’s authority, other officials or other persons. The most harmful consequences of unsubstantiated illegal law-enforcement decisions made by law-enforcers due to mistakes and quasi-mistakes are identified: a) devaluation of the criminal law; b) degradation of the investigative and judicial system; c) the loss of people’s faith in the validity of the state authorities’ decisions, decency of the authorities, and justice.Practical significance: the main provisions and conclusions should be used to improve the investigative and judicial activities at law-enforcement and managerial levels when implementing the criminal law policy of the state.